International Frontal Sinus Anatomy Classification (IFAC): evaluation of frontoethmoidal cells prevalence in a Brazilian population - Ruth Ellen Fernandes de Castro Dantas Braz; Mariana Dalbo Contrera Toro; Emerson Taro Inoue Sakuma; Vinicius Silles Brandão Machado; Eulalia Sakano (Brazilian Journal of Otorhinolaryngology, 2023)
Objectives: The aim of this study was to evaluate the prevalence of the frontal cell variants according to International Frontal Sinus Anatomy Classification (IFAC), in the population of a Brazilian tertiary hospital, and analyze the reliability of the classification between observers. Methods: A cross-sectional study in the Hospital de Clínicas of the State University of Campinas, Brazil. One hundred and three Computed Tomography's (CTs) were evaluated by radiologists and otorhinolaryngologist to estimate the prevalence of frontoethmoidal cells according to the IFAC. Intraclass Correlation Coefficient (ICC) among examinators was used to evaluate reliability of this findings. Results: 103 CT scans, totaling 206 sides, were evaluated independently. The agger nasi cell was the most prevalent, present in 95.63% of cases, 37.86% of the exams contained supra agger cells, frontal supra agger cell showed prevalence 37.37%; suprabular cell was present in 77.18% of the sides. As for the frontal suprabular cell, the prevalence was 30.09%, the supraorbital ethmoid cell was present in 32.03%, and frontal septal cell had a 33.49% prevalence. The ICC among the evaluators was classified as “good reliability” or “excellent reliability” for all cells. Conclusion: This study describes the frontal cell prevalence among a population in tertiary Brazilian hospital, using the IFAC. This classification had a high ICC. Level of evidence: Level 2: Individual cross-sectional study with consistently applied reference standard and blinding.